2022
DOI: 10.1007/s10803-022-05796-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Robot-Assisted Psychological Intervention for Children with Autism Spectrum Disorder

Abstract: Difficulties with social interaction characterise children with Autism Spectrum Disorders and have a negative impact in their everyday life. Integrating a social-humanoid robot within the standard clinical treatment has been proven promising. The main aim of this randomised controlled study was to evaluate the effectiveness of a robot-assisted psychosocial intervention and the secondary aim was to investigate potential differences between a robot-assisted intervention group and a control group receiving interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
0
11
1
Order By: Relevance
“…The auditory performance results of the present study show promise for conducting the PICKA psychophysics tasks, insofar as the voice cue sensitivity and voice gender categorisation tests are concerned on Sam. Furthermore, our results contribute to the growing potential of using humanoid robots for both learning and testing applications [ 34 – 36 , 75 , 76 ], also for specific target groups and rehabilitation applications (e.g., [ 43 , 77 , 78 ]), and our general understanding of speech communication and voice perception in HRI, an increasingly relevant topic for social robots [ 1 , 13 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 79%
“…The auditory performance results of the present study show promise for conducting the PICKA psychophysics tasks, insofar as the voice cue sensitivity and voice gender categorisation tests are concerned on Sam. Furthermore, our results contribute to the growing potential of using humanoid robots for both learning and testing applications [ 34 – 36 , 75 , 76 ], also for specific target groups and rehabilitation applications (e.g., [ 43 , 77 , 78 ]), and our general understanding of speech communication and voice perception in HRI, an increasingly relevant topic for social robots [ 1 , 13 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 79%
“…Recent studies have increasingly applied robots in educational situations ( Pandey and Gelin, 2017 ), including the teaching of self-regulation skills ( Holtz and Lehman, 1995 ; Carlson, 2005 ; Lillard et al, 2015 ; Holeva et al, 2021 ). An important aspect of DG, however, is the ability to develop strategies to counter the effects of any frustration or preference reversal that may be occurring while actively choosing to wait for a preferred but delayed reward.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to obtain the robot’s reward in this variant of the game, children are required to press their button in turn with another child, thus teaching them to learn self-regulation skills. Holeva et al (2021) investigated the effects of robot-assisted relaxation training for children and its effects on emotional self-regulation. Lastly, Silva et al (2018) used a robotic dog as a control for novelty effects as children with autism interacted with a live dog.…”
Section: Introductionmentioning
confidence: 99%
“…Another study investigated the effectiveness of robot interventions for cognitive and psychological outcomes among older adults with cognitive impairment and found that robot interventions were effective in improving cognitive and psychological outcomes [ 21 ]. Additionally, a case study was conducted to evaluate the effectiveness of a robot-assisted psychological intervention for children with autism spectrum disorder, which showed positive results [ 22 ]. While these studies provide evidence of the efficacy of robotic interventions, it is essential to note that each case is unique, and outcomes may vary depending on the individual patient and the specific intervention being performed.…”
Section: Reviewmentioning
confidence: 99%